Magnetic properties of TbFe thin films under applied stress - Pasquale, M; Infortuna, A; Martino, L; Sasso, C; Beatrice, C; Lim, SH (ELSEVIER SCIENCE BV, 2000)
The magnetic properties of a set of TbxFe1-x magnetostrictive thin films are measured under applied stress in a cantilever configuration. The 1 mu m thick films are produced on 200 mu m thick Si (100) substrates by magnetron sputtering in Ar atmosphere. Magnetic characterization is obtained with complementary fluxmetric and magneto-optic Kerr effect methods. The role of stress-induced anisotropy is discussed, with reference to the intrinsic anisotropy which can lie in-plane or out-of-plane depending on composition. An optimal film composition at x = 54 at% is determined for sensor applications requiring magnetic softness and stress sensitivity. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: MAGNETOSTRICTION